Peer learning in the UNSW Medicine program. Issue 1 (December 2015) - Scicluna, Helen; O'Sullivan, Anthony; Boyle, Patrick; Jones, Philip; McNeil, H.
Abstract Background The UNSW Australia Medicine program explicitly structures peer learning in program wide mixing of students where students from two adjoining cohorts complete the same course together, including all learning activities and assessment. The purpose of this evaluation is to explore the student experience of peer learning and determine benefits and concerns for junior and senior students. Methods All medical students at UNSW Australia in 2012 (n  = 1608) were invited to complete the Peer Learning Questionnaire consisting of 26 fixed-response items and 2 open-ended items exploring vertical integration and near-peer teaching. Assessment data from vertically integrated and non-vertically integrated courses were compared for the period 2011–2013. Results We received valid responses from 20 % of medical students (n  = 328). Eighty percent of respondents were positive about their experience of vertical integration. Year 1 students reported that second year students provided guidance and reassurance (87.8 %), whilst year 2 students reported that the senior role helped them to improve their own understanding, communication and confidence (84 %). Vertical integration had little effect on examination performance and failure rates. Conclusions This evaluation demonstrates that vertical integration of students who are one year apart and completing the same course leads to positive outcomes for the student experience of learning. Students benefit through deeper learning and the development of leadership qualities within teams. These results are relevant not only for medical education, but also for other professional higher education programs.